Analisis Keterampilan Proses Sains Calon Guru Biologi Terhadap HOTS: Analysis of Pre-service Teachers Biology Science Process Skills towards HOTS - Lutphi Safahi; Arum Pusporini; Susilo Susilo; Budhi Akbar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
The low problem-solving ability in understanding biology lessons makes biology lessons difficult for some prospective teachers to learn. This study aims to determine the contribution of science process skills to higher-order thinking skills. This study uses quantitative methods to analyse the HOTS skills of prospective biology teachers. The quantitative descriptive method used in this study. Data collected from 59 respondents through the Saturated Sampling technique. The instrument used was 54 multiple choice questions with indicators of science process skills and higher-order thinking skills. The data obtained is processed quantitatively with Microsoft Excel. Prospective Biology teachers have the contribution of science process skills with a high level of ability of 13% and a contribution is known. This research proves that the contribution of science process skills to prospective biology teachers to higher-level thinking skills has low categorisation. Keywords: Science Process Skills; Pre-service Teachers Biology; High-level Thinking Ability; biology lessons. Abstrak. Rendahnya kemampuan pemecahan masalah dalam memahami pelajaran biologi menyebabkan pelajaran biologi menjadi sulit dipelajari oleh sebagian calon guru. Studi ini bertujuan untuk mengetahui kontribusi keterampilan proses sains terhadap kemampuan berpikir tingkat tinggi. Penelitian ini menggunakan metode kuantitatif untuk menganalisa keterampilan HOTS calon guru biologi. Metode penelitian yang digunakan adalah diskriptif kuantitatif. Data dikumpulkan dengan sampel sebanyak 59 mahasiswa melalui teknik Sampling Jenuh. Instrumen yang digunakan berupa 54 soal pilihan ganda dengan indikator keterampilan proses sains dan kemampuan berpikir tingkat tinggi. Data yang diperoleh diolah secara kuantitatif dengan Microsoft Excel. Calon guru Biologi memiliki hasil kontribusi keterampilan proses sains dengan kemampuan berpikir tingkat tinggi sebesar 13% dan diketahui adanya kontribusi. Penelitian ini membuktikan bahwa kontribusi keterampilan proses sains calon guru biologi terhadap kemampuan berpikir tingkat tinggi memiliki kategori rendah. Kata kunci: Keterampilan Proses Sains; Calon guru biologi; HOTS; Pelajaran biologi.